Assessment of cytokine values in serum by RT-PCR in HIV-1 infected individuals with and without highly active anti-retroviral therapy (HAART) - Meira, D. A. [UNESP]; Ramb, Almeida [UNESP]; Barbosa, A. N. [UNESP]; De Souza, L. R. [UNESP]; Tet, Olivo [UNESP]; Henriques, R. M.S. [UNESP]; Golim, M. A. [UNESP]; Araújo, J. R.J.P. [UNESP]; Nagoshi, L. R. [UNESP]; Orikaza, C. M. [UNESP]; Calvi, S. A. [UNESP] (FapUNIFESP (SciELO), 2008)
A cross-sectional study was performed on HIV-1 infected individuals with or without antiretroviral treatment (ARV) in the AIDS Day Hospital, Botucatu Medical School, UNESP. Between August 2004 and October 2005, 73 HIV-1 infected individuals were divided into three groups: infected individuals with or without AIDS who had never received ARV (G1 = 15); patients on HAART that had had plasma HIV-1 RNA viral load (VL) equal to or greater than 50 copies/mL (G2 = 27); and patients on HAART with undetectable VL for at least the past six months (G3 = 31). There was also an additional group that comprised blood donors without any sign of the disease and with negative HIV serum tests (G4 = 20), which was the control group. Serum cytokine levels (values in pg/mL) were measured by enzyme-linked immunosorbent assay (ELISA) and specific mRNA expression by reverse transcription polymerase chain reaction (RT-PCR). Both techniques were performed on the four groups for TNF-α, IL-2, INF-γ, IL-4 and IL-10. All patients were submitted to VL determination and CD4+ and CD8+T lymphocyte counts. The analysis of the results revealed a significant comparison among groups for both methods and an association between the latter (> 80% -r2 > 0.80). There was only one exception, in control individuals for IL-2 by ELISA. The cytokine profiles, in both methods, for the three patient groups, were mature Th-0. The behaviors of IL-2 and INF-γ required emphasis due to consequent expression of dominant Th profile. Both methods showed low IL-2 and high mean values of INF-γ in the three groups. Several authors have recently drawn attention to the substantial apoptosis of infected and non-infected CD4+T cells, mainly during primary infection, persisting only in those with INF-γ phenotype producer and not IL-2. HIV infected individuals submitted to HAART are expected to produce IL-2 in an attempt to present Th-1 profile, but in most cases this did not occur.
Keywords: AIDS; Apoptosis; Cytokines; ELISA; HAART; HIV; RT-PCR